MHC IMMUNOGENETICS INFLUENCES THE REPRODUCTION IN SHEEP - MIR, MANZOOR R; GELDERMANN, H; WANl, G M (The Indian Journal of Animal Reproduction, 2023)
Experiment was conducted in four consecutive lambings to establish feta-maternal immune response in asheep flock of 639 animals. A total of 16 DRB1 microsatellite alleles3 , ranging between 353 and 857 bp weredetected which were associated with variable reproductive performances among males and females. Ewes carrying411 bp allele exhibited higher values for all recorded fertility traits (p
Keywords: Sheep; DRB; Microsatellite; Fertility; QTL